Does neuroticism disrupt the psychological benefits of nostalgia? a meta-analytic test. Issue 2 (March 2021) - Frankenbach, Julius; Wildschut, Tim; Juhl, Jacob; Sedikides, Constantine
Nostalgia, a sentimental longing or wistful affection for the past, confers self-oriented, existential, and social benefits. We examined whether nostalgic engagement is less beneficial for individuals who are high in neuroticism (i.e. emotionally unstable and prone to negative affect). Specifically, we tested whether the benefits of experimentally induced nostalgia are moderated by trait-level neuroticism. To address this issue, we conducted a high-powered individual participant data meta-analysis ( N = 3556, k = 19). We found that the benefits of nostalgia were not significantly moderated by neuroticism, as they emerged for both high and low neurotics. This finding upheld when the self-oriented, existential, and social benefits of nostalgia were analysed jointly and when they were analysed separately. Taken together, individuals high and low in neuroticism are equally likely to benefit psychologically from engagement in nostalgic reverie.